An Exploratory study of efficacy of Aslussoos (Glycyrrhiza glabra Linn)) in Chronic Bronchitis (Muzmin iltehab sho'b)-A Cohort Study - Mohd. Wajid, Shaikh; Shaikh Altaf Maniyar , Shaikh Mudassar; Ahmad, Nisar; Nasreen, Faizana; Gulam Sultani , Jameelur Rehman; Noor , . Lamatun (Journal of Neonatal Surgery, 2024)
Chronic bronchitis (Muzmin Iltehab Sho'b) is a major respiratory condition characterized by persistent cough and sputum production for at least three months in two consecutive years. It commonly affects individuals exposed to smoking, dust, fumes, and environmental pollutants. Modern pharmacological treatments often provide symptomatic relief but are limited by adverse effects and cannot be used safely for long durations. Unani medicine describes chronic bronchitis as a condition arising from accumulation of viscid phlegm in bronchi, and traditionally recommends demulcent, expectorant, and anti-inflammatory herbs like Aslussoos (Glycyrrhiza glabra Linn). The present open-label, randomized cohort study evaluated the efficacy of Aslussoos in 30 clinically diagnosed patients aged 40–60 years. Patients received Sufoof-e-Aslussoos (3 g twice daily) for 30 days. Assessments included clinical symptoms, spirometry, and hematological investigations. The therapy showed encouraging results, particularly in reducing cough, sputum production, and breathing difficulty, with no adverse effects reported. The study validates Aslussoos as a safe, beneficial option for managing chronic bronchitis within the framework of Unani medicine..